LEGAL ANALYSIS OF LOCAL GOVERNMENT SUPPORT IN THE DISTRIBUTION OF PARTICIPANTS RECEIVING CONTRIBUTION ASSISTANCE TO PRIVATE PRIMARY HEALTH CARE FACILITIES - Diah Arimbi; Aliesa Amantita; Lily Andayani (LPPM STIH Putri Maharaja, 2025)
Abstract Local governments play a crucial role in managing the National Health Insurance (Jaminan Kesehatan Nasional, JKN). Despite various advancements achieved, issues surrounding the uneven distribution of Participants Receiving Premium Assistance (Penerima Bantuan Iuran, PBI) persist and fail to meet the principles of justice. This situation also threatens the rights of JKN participants. The objective of this research is to evaluate the support provided by local governments to the JKN program. The research methodology employs a juridical normative approach. Research findings reveal an agreement that all PBI participants must be registered with Community Health Centers (Puskesmas), resulting in limited freedom for PBI participants, including those who are impoverished and underprivileged, to select healthcare facilities in accordance with the provisions of the Health Law. Legally, local government support for the JKN program is explicitly stated in the Health Insurance Law (Undang-Undang BPJS) and Government Regulation Number 82 of 2018. However, the distribution of PBI participants is still not fully implemented. AbstrakPemerintah daerah memiliki peran yang sangat penting dalam mengelola Jaminan Kesehatan Nasional (JKN). Meskipun telah dicapai berbagai kemajuan, permasalahan dalam distribusi peserta Penerima Bantuan Iuran (PBI) yang belum merata dan belum memenuhi prinsip keadilan tetap menjadi isu yang perlu diatasi. Situasi ini juga mengancam hak-hak peserta JKN. Tujuan dari penelitian ini adalah untuk mengevaluasi dukungan yang diberikan oleh pemerintah daerah terhadap program JKN. Metodologi penelitian menggunakan pendekatan yuridis normatif. Hasil penelitian menunjukkan bahwa telah ada kesepakatan bahwa seluruh peserta PBI wajib didaftarkan di Puskesmas, yang pada gilirannya mengakibatkan peserta PBI, termasuk mereka yang berstatus miskin dan tidak mampu, tidak memiliki kebebasan untuk memilih fasilitas kesehatan sesuai dengan ketentuan dalam Undang-Undang Kesehatan. Dari segi hukum, dukungan pemerintah daerah terhadap program JKN jelas tertera dalam Undang-Undang BPJS dan Peraturan Pemerintah Nomor 82 Tahun 2018. Namun, distribusi peserta PBI masih belum sepenuhnya terlaksana.